Clinical Arterial Spin-Labeling MR Imaging to Screen for Typical and Atypical Neurodegenerative Disease in the New Era of Alzheimer Treatment - Lee, Kevin; Mahmud, Meem; Marx, Darby; Yasen, Weiye; Sharma, Omna; Ivanidze, Jana; Zan, Elcin; Zhou, Liangdong; Li, Yi; de Leon, Mony J.; Nordvig, Anna S.; Chiang, Gloria C. (American Journal of Neuroradiology, 2024)
The clinical standard of care in the diagnosis of neurodegenerative diseases relies on [18F] FDG-PET/CT or PET MR imaging. Limitations of FDG-PET include cost, the need for IV access, radiation exposure, and availability. Arterial spin-labeling MR imaging has been shown in research settings to be useful as a proxy for FDG-PET in differentiating Alzheimer disease from frontotemporal dementia. However, it is not yet widely used in clinical practice, except in cerebrovascular disease. Here, we present 7 patients, imaged with our routine clinical protocol with diverse presentations of Alzheimer disease and other neurodegenerative diseases, in whom arterial spin-labeling–derived reduced CBF correlated with hypometabolism or amyloid/tau deposition on PET. Our case series illustrates the clinical diagnostic utility of arterial spin-labeling MR imaging as a fast, accessible, and noncontrast screening tool for neurodegenerative disease. Arterial spin-labeling MR imaging can guide patient selection for subsequent PET or fluid biomarker work-up, as well as for possible therapy with antiamyloid monoclonal antibodies.ADAlzheimer diseaseADLsactivities of daily livingASLarterial spin-labelingCIcognitive impairmentCOVID-19coronavirus 2019lvPPAlogopenic variant progressive aphasiaMCImild cognitive impairmentMoCAMontreal Cognitive AssessmentPCAposterior cortical atrophy